IMPLEMENTASI DISCHARGE PLANNING TENTANG PERSONAL HYGIENE PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Novi Arista Widya Astuti; Nina Fentiana; Ika Ariyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Ischemic stroke is a serious non-communicable disease worldwide, characterized by functional impairment affecting the brain, such as nerve paralysis caused by a lack of oxygen supply to the brain. This study aims to describe the implementation of discharge planning regarding personal hygiene for ischemic stroke patients. This research used a case study method with a nursing care approach, including assessment, diagnosis. intervention, implementation, and evaluation. Data were collected using observation sheets and questionnaires. The results of this study showed an increase in knowledge regarding discharge planning on personal hygiene in both patients: in the first patient, knowledge level increased from 46% (poor) to 86% (good), and in the second patient, knowledge level increased from 46% (poor) to 86% (good). It can be conclude that discharge planning related to personal hygiene is effective in improving the understanding and ability of families to care for patients at home, thereby helping reduce the risk of complications. It is recommended that families regularly apply personal hygiene practices to prevent complications such as skin infections and body odor